2015
DOI: 10.19026/ajfst.7.1301
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Antioxidant Activity of Milk Samples Collected from Five Goat Breeds in Malaysia

Abstract: Five different goat breeds (Saanen, Kacang, Jamnapari, Boer and a crossbred of Jamnapari and Saanen) were obtained from one farm in Bandar Baru Bangi. The aim of this study was to determine the physicochemical properties and antioxidant capacity based on TPC, FRAP and DPPH. Goat milk samples were collected during the same lactation period (middle lactation) and were subsequently compared with cow milk. The results of the study showed that goat milk exhibited a significantly higher (p<0.05) antioxidant capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
1
13
0
3
Order By: Relevance
“…[51,52] The milk samples of Saanen breed had the lowest value of fat (2.53%), while the Jamnapari milk presented the highest fat (4.20%) and protein (3.73%) content. The percentage of milk fat for all goat breeds were in the range reported by Alyaqoubi et al [53] which was between 2.43% and 4.43%. In addition, goat milk contained 3.4% protein, 3.8% fat, 4.1% lactose, 0.8% ash [54] and 87% water.…”
Section: Fat Protein and Lactose Analysissupporting
confidence: 61%
“…[51,52] The milk samples of Saanen breed had the lowest value of fat (2.53%), while the Jamnapari milk presented the highest fat (4.20%) and protein (3.73%) content. The percentage of milk fat for all goat breeds were in the range reported by Alyaqoubi et al [53] which was between 2.43% and 4.43%. In addition, goat milk contained 3.4% protein, 3.8% fat, 4.1% lactose, 0.8% ash [54] and 87% water.…”
Section: Fat Protein and Lactose Analysissupporting
confidence: 61%
“…Previous study reported that Jamnapari breed had 81.28% of moisture and 0.96% of ash content. [17] Even though similar environmental setting and breed were applied in both studies, other factors, such as age of goat, body size and weight, udder size, diet, and lactation stage, can cause variation in milk constituents [18] .…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Recently, Alyaqoubi et al . (2015) determined the physicochemical properties and antioxidant activity of milk from five different goat breeds and Lai et al .…”
Section: Introductionmentioning
confidence: 99%